2008
DOI: 10.1159/000151290
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Platelet-Rich Plasma on Chondrogenic Differentiation and Proliferation of Chondrocytes and Mesenchymal Stem Cells

Abstract: Background/Aims: Autologous chondrocyte (CC) transplantation has the disadvantages of requiring two surgical interventions and in vitro expansion of cells, implying the risk of cellular dedifferentiation. Our clinical aim is to develop a one-step procedure for autologous CC transplantation, i.e. harvesting, isolation and reimplantation of CC performed in one single surgical procedure. Platelet-rich plasma (PRP) is a source of autologous growth factors reported to have mitogenic effects. The objective of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
122
2
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(145 citation statements)
references
References 88 publications
15
122
2
4
Order By: Relevance
“…Our explanation was already supported by Gulotta et al, who suggested that the majority of patients who undergo this surgery experience immediate chondrocyte necrosis after surgery, followed by a reincorporation of their grafts [11]. In this process, PRP may have a reinforcement on chondral regeneration and proliferation of chondrocytes as a biologic inducer in the short term [16,26].…”
Section: Discussionmentioning
confidence: 53%
“…Our explanation was already supported by Gulotta et al, who suggested that the majority of patients who undergo this surgery experience immediate chondrocyte necrosis after surgery, followed by a reincorporation of their grafts [11]. In this process, PRP may have a reinforcement on chondral regeneration and proliferation of chondrocytes as a biologic inducer in the short term [16,26].…”
Section: Discussionmentioning
confidence: 53%
“…Interestingly, PRP or platelet supernatant stimulates the proliferation of articular chondrocytes, but has no effect on chondrocyte differentiation or even leads to dedifferentiation towards a fibroid phenotype as shown in bovine, ovine and human chondrocytes. [32][33][34] In contrast, PRP also stimulated the proliferation of mesenchymal stem cells but did not induce stem cell differentiation as shown in the ovine model. 34 In human mesenchymal stem cells, buffered PRP enhanced stem cell proliferation and induced the differentiation along the osteogenic and chondrogenic lineage as shown by the induction of the transcription factors Runx2 and Sox9 in monolayer cultures.…”
Section: Discussionmentioning
confidence: 91%
“…[32][33][34] In contrast, PRP also stimulated the proliferation of mesenchymal stem cells but did not induce stem cell differentiation as shown in the ovine model. 34 In human mesenchymal stem cells, buffered PRP enhanced stem cell proliferation and induced the differentiation along the osteogenic and chondrogenic lineage as shown by the induction of the transcription factors Runx2 and Sox9 in monolayer cultures. 35 As shown here, in high-density pellet cultures, PRP induced the chondrogenic differentiation but not the development along the osteogenic or adipogenic lineage.…”
Section: Discussionmentioning
confidence: 91%
“…Drengk et al (2009) demonstrated that activated PRP enhanced cell proliferation in sheep bone marrow-derived mesenchymal stromal cells (BMSCs). Another study reported that inactivated PRP could accelerate cell proliferation in human BMSCs (Xie et al 2014).…”
Section: Discussionmentioning
confidence: 99%